2019
DOI: 10.1080/26395940.2019.1679041
|View full text |Cite
|
Sign up to set email alerts
|

Development of a predictive tool for rapid assessment of soil total nitrogen in wheat-corn double cropping system with hyperspectral data

Abstract: Precision farming based on soil total nitrogen status is crucial to informed fertilization strategies while enhancing environmental quality of agricultural ecosystems. Hyperspectral technology was applied for rapid assessment of soil total nitrogen content in a long-term fertilization experiment of wheat-corn rotation system. The first-order derivative of squared spectra and Soil Adjusted Spectral Index transformation provided the highest correlation with soil total nitrogen contents. Inversion modeling result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For the problem of detecting anomalies in TN data, we proposed a method for identifying TN outliers by combining the isolated forest algorithm and the local spatial autocorrelation analysis method and identified the outliers of TN data in Yunnan Province in 2009 and reached the following conclusions: (1) The overall situation of TN content in Yunnan Province is good, and at the same time, TN is positively correlated with SOM, PH, AP and AK relationship, and had a strong correlation with soil organic matter (R = 0.74). (2) The proposed method has high detection validity and accuracy in detecting TN anomalies, and in the detection effect of 2009 TN data in Yunnan Province, it showed that the TR could reach 99.97%, and the FNR was 0.01%. (3) Comparing the proposed method with the independent isolated forest (FNR = 4.76%), boxplot (FNR = 3.90%), OneClassSVM (FNR = 4.77%) and the combination method of boxplot, OneClassSVM combined with spatial analysis, respectively, the results show that the proposed method (FNR = 0.01%) is better than the single method and other combination methods.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…For the problem of detecting anomalies in TN data, we proposed a method for identifying TN outliers by combining the isolated forest algorithm and the local spatial autocorrelation analysis method and identified the outliers of TN data in Yunnan Province in 2009 and reached the following conclusions: (1) The overall situation of TN content in Yunnan Province is good, and at the same time, TN is positively correlated with SOM, PH, AP and AK relationship, and had a strong correlation with soil organic matter (R = 0.74). (2) The proposed method has high detection validity and accuracy in detecting TN anomalies, and in the detection effect of 2009 TN data in Yunnan Province, it showed that the TR could reach 99.97%, and the FNR was 0.01%. (3) Comparing the proposed method with the independent isolated forest (FNR = 4.76%), boxplot (FNR = 3.90%), OneClassSVM (FNR = 4.77%) and the combination method of boxplot, OneClassSVM combined with spatial analysis, respectively, the results show that the proposed method (FNR = 0.01%) is better than the single method and other combination methods.…”
Section: Discussionmentioning
confidence: 86%
“…Soil total nitrogen is the sum of the different forms of nitrogen in the soil, including organic and inorganic nitrogen [1], and is an important nutrient affecting grain yield and quality, with too much or too little nitrogen being detrimental to crop production [2,3]. Soil total nitrogen is usually determined by micro-Kjeldahl, semi-micro-Kjeldahl and micropotassium sulphate methods [4], and the results can provide an important basis for soil formulation and fertiliser application, help improve nitrogen fertiliser use and reduce pollution of agricultural surface water sources [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, decisions regarding fertility, regions of improvement, potential crop yields etc. can be taken with technological evidence [15].…”
Section: Resultsmentioning
confidence: 99%
“…Sweet corn is a widely cultivated food crop because it is rich Sensors 2022, 22, 1822 2 of 17 in vitamins, amino acids and so on, making it more and more popular [13,14]. Nitrogen, phosphorus and potassium in sweet corn are important nutrients for its growth, which have great influence on its growth, yield and quality [15][16][17]. Because the traditional diagnosis of maize nutrient elements adopts chemical methods, a large number of corn samples need to be picked, and complicated chemical testing is required, which takes a long time and will cause damage to the plant [18].…”
Section: Introductionmentioning
confidence: 99%